Fast Access to 5-Hydroxymethyl Derivatives of 2′-Deoxyuridine Promoted by Acidic Amberlyst 15 Resin - Liu, D.; Monfret, O.; Bourdreux, Y.; Urban, D.; Guianvarc’h, D.; Doisneau, G. (Synlett, 2022)
5-Hydroxymethyl derivatives of pyrimidine nucleosides are an important class of biologically relevant compounds. In addition, such derivatives and related compounds can be functionalized for various applications. To enable fast, economical, and efficient access to 5-hydroxymethylated derivatives of 2′-deoxyuridine, we report a method for the O-5 chemoselective transformation of unprotected 5-(hydroxymethyl)-2′-deoxyuridine through selective etherification in the presence of an alcohol promoted by acidic Amberlyst 15 resin at room temperature. These mild conditions constitute a significant improvement compared with the harsh conditions previously described. Applied to various primary or secondary alcohols, the reaction showed a broad substrate scope, and 24 C(5)-modified derivatives of 5hmdU were synthesized with good isolated yields. Notably, this efficient procedure represents a straightforward method for preparing (i) several useful building blocks for subsequent chemical ligation by using CuAAC reactions; (ii) natural hypermodified thymidines and analogues, including glycosylated derivatives; and (iii) cyanoethyl-protected 5hmdU, useful for solid-phase oligonucleotide syntheses.
Keywords: hydroxymethyldeoxyuridine; nucleosides; hydroxymethylation; pyrimidines; etherification; chemoselectivity